2019
DOI: 10.3390/su11174712
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Factors Influencing Transport Sector CO2 Emissions and Their Efficiency in Central China

Abstract: The fast development of the transport sector has resulted in high energy consumption and carbon dioxide (CO2) emissions in China. Though existing studies are concerned with the factors influencing transport sector CO2 emissions at the national level (or in megacities), little attention has been paid to the comprehensive impact of socio-economic, urban form, and transportation development on transport sector carbon emissions and emissions efficiency in central China. This paper examines the comprehensive impact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…In this study, we classified influencing factors into three categories: human activities, vegetation, and meteorological factors [57]. Areas with higher population density exhibit significantly higher carbon dioxide concentrations, as the distribution of emission sources such as industry and transportation directly affects carbon dioxide concentrations [58,59]. Vegetation conditions directly affect the absorption of carbon dioxide by vegetation and also influence the exchange processes between vegetation and the atmosphere.…”
Section: Influencing Factorsmentioning
confidence: 99%
“…In this study, we classified influencing factors into three categories: human activities, vegetation, and meteorological factors [57]. Areas with higher population density exhibit significantly higher carbon dioxide concentrations, as the distribution of emission sources such as industry and transportation directly affects carbon dioxide concentrations [58,59]. Vegetation conditions directly affect the absorption of carbon dioxide by vegetation and also influence the exchange processes between vegetation and the atmosphere.…”
Section: Influencing Factorsmentioning
confidence: 99%
“…Compact cities are characterized by aggregated functions, a high density, and a strong transportation network [208]. Their advantages include short travel distances and travel times, low-carbon travel, mixed land use, the high accessibility of facilities, high population density and development, and an adequate public transport system [63,66,113]. Fewer private cars are used due to less urban sprawl and suburbanization, thereby reducing fossil energy consumption and vehicle emissions [56,97,209].…”
Section: Urban Landscape Designmentioning
confidence: 99%
“…Dense public transport facilities (bus stops, parking lots, etc.) may increase the probability of residents traveling and driving, and an extensive road transport network may lead to the excessive expansion of the city, thereby increasing vehicle emissions [42,66]. Although the degree of urban land aggregation is improved, unreasonable resource allocation may increase carbon emissions [47].…”
Section: Urban Landscape Designmentioning
confidence: 99%
“…Many previous studies [43][44][45] have been concerned with urbanization impact on transport CO 2 emissions. Hasan et al [44] result indicated that, with the increase of the urban population, CO 2 emissions from the New Zealand transport sector have increased.…”
Section: Literature Reviewmentioning
confidence: 99%